Các yếu tố tác động đến xung đột tâm lí giữa học sinh trung học phổ thông và cha mẹ: Một nghiên cứu tại thành phố Hà Nội - Nguyễn, Trần Thiên Lam; Lê, Linh Dung; Nguyễn, Thị Lán; Nguyễn Thị Hồng Vân (Tạp chí Giáo dục, 2025)
The authors conducted this study given the reality that conflicts between high school students and their parents have been on the rise. Previous research has not fully examined the impact of various factors on these conflicts. By combining qualitative research and quantitative analysis on a sample of 510 high school students and 510 parents in Hanoi, the authors examined the impact of five factors on the conflict between high school students and their parents, including: contradictions, “ego”, psychological and physiological characteristics of high school students, negative parenting styles, and limited communication skills and emotional regulation. Eventually, “ego” was found to have the strongest impact. The study results pave the way for a more comprehensive approach to addressing the factors that contribute to conflicts between high school students and their parents. The authors suggest several measures to prevent these conflicts, including resolving contradictions early, properly managing “ego” and developing self-worth, along with other targeted solutions for specific groups.